REFORMULATION OF THE INSTITUTIONAL FUNCTIONS AND AUTHORITIES OF THE NATIONAL COMMISSION ON HUMAN RIGHTS - Aris Septiono (Universitas 17 Agustus 1945 Semarang, 2023)
The handling of serious human rights violations has become a strategic and prioritized issue for the National Commission on Human Rights (Komnas HAM). This conceptual article aims to evaluate law enforcement efforts regarding cases of serious human rights violations handled by Komnas HAM and identify the obstacles and challenges faced in the process of resolving these cases. The research findings indicate that Komnas HAM has completed investigations into 12 cases of serious human rights violations and forwarded them to the Attorney General's Office as the investigator and public prosecutor. However, the legal process for these cases has stagnated, especially those already decided by the Ad Hoc Human Rights Court, such as the cases of Timor Timur, Tanjung Priok, and Abepura, where the defendants were eventually acquitted. The main challenges faced are the limited willingness and capacity of the Indonesian State to resolve cases of serious human rights violations. Additionally, weaknesses in legal aspects and the political will of the Government and Law Enforcement Agencies also influence the law enforcement process concerning serious human rights violations. Therefore, the novelty offered lies in the importance of a comprehensive evaluation of respect, protection, and fulfillment of human rights as a critical step to enhance the effectiveness of law enforcement regarding serious human rights violations. A reassessment of strengthening Komnas HAM's authority is required to ensure legally binding measures and clear consequences for those who do not comply with Komnas HAM's recommendations.